2021
DOI: 10.1007/s11684-021-0862-5
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of insulin resistance in obesity: a role of ATP

Abstract: Obesity increases the risk of type 2 diabetes through the induction of insulin resistance. The mechanism of insulin resistance has been extensively investigated for more than 60 years, but the essential pathogenic signal remains missing. Existing hypotheses include inflammation, mitochondrial dysfunction, hyperinsulinemia, hyperglucagonemia, glucotoxicity, and lipotoxicity. Drug discoveries based on these hypotheses are unsuccessful in the development of new medicines. In this review, multidisciplinary literat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
29
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(29 citation statements)
references
References 104 publications
0
29
0
Order By: Relevance
“…We found that the expression of ATPase gene related to insulin secretion pathway was significantly higher in VAT than in SAT. ATP is a major signal of pancreatic IR ( Ye, 2021 ). In obesity, ATP overproduction promotes systemic IR through a several mechanisms, such as inhibition of AMPK, Mtor induction, hyperinsulinemia, hyper glucagon and mitochondrial dysfunction.…”
Section: Discussionmentioning
confidence: 99%
“…We found that the expression of ATPase gene related to insulin secretion pathway was significantly higher in VAT than in SAT. ATP is a major signal of pancreatic IR ( Ye, 2021 ). In obesity, ATP overproduction promotes systemic IR through a several mechanisms, such as inhibition of AMPK, Mtor induction, hyperinsulinemia, hyper glucagon and mitochondrial dysfunction.…”
Section: Discussionmentioning
confidence: 99%
“…Under obese circumstance, mitochondrial overheating is induced by oversupply of substrate to mitochondria in insulin-sensitive cells. Mitochondrial overheating brings about overproduction of ATP and the inhibition of AMPK ( Ye, 2021 ). Meanwhile, obesity is often accompanied by the hyposecretion of adiponectin, an endogenous AMPK activator ( Li et al, 2021 ).…”
Section: Amp-activated Protein Kinase In the Pathophysiology Of Intervertebral Disc Degenerationmentioning
confidence: 99%
“…Meanwhile, obesity is often accompanied by the hyposecretion of adiponectin, an endogenous AMPK activator ( Li et al, 2021 ). Through the modulation of AMPK activity, obesity results in the systemic insulin resistance and hyperglycemia ( Ye, 2021 ). As reported, ageing process is always accompanied with the reduction of AMPK activation ( Salminen et al, 2016 ).…”
Section: Amp-activated Protein Kinase In the Pathophysiology Of Intervertebral Disc Degenerationmentioning
confidence: 99%
“…This function is induced by substrates, hormones, and energy demand as discussed above. In a recent review, excessive substrate availability in obesity has been proposed as a major factor contributing to mitochondrial overproduction of ATP in the mechanism of insulin resistance (134). The insulin resistance occurs following ATP surplus in multiple tissues, in which ATP production exceeds demand (134).…”
Section: Androgen and Estrogen Synergy In Mitochondrial Overactivationmentioning
confidence: 99%
“…In a recent review, excessive substrate availability in obesity has been proposed as a major factor contributing to mitochondrial overproduction of ATP in the mechanism of insulin resistance (134). The insulin resistance occurs following ATP surplus in multiple tissues, in which ATP production exceeds demand (134). ATP surplus in the pancreatic b-cells leads to more secretion of insulin for hyperinsulinemia.…”
Section: Androgen and Estrogen Synergy In Mitochondrial Overactivationmentioning
confidence: 99%